ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI LADA DI KECAMATAN ABUNG BARAT KABUPATEN LAMPUNG UTARA - Putri, Mutiara; Prasmatiwi, Fembriarti Erry; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The purposes of this research are to find out the income of pepper farming, household income, level of household welfare, and factors that affect the welfare of pepper farmer households in Abung Barat Sub-District. The location was determined purposively with the consideration that Abung Barat Sub-District is the center of black pepper production. The number of respondents in this research is 63 respondents taken randomly. Data were collected from April to May 2019. The analytical methods used are farming analysis, the analysis of Sajogyo and Subyective welfare levels, and binary logit analysis. The results showed that average income of pepper farming is IDR8,356,590.51/year, average household income is IDR20,055,616.61/year, based on the criteria of Sajogyo 61.90 percent of the respondent pepper farmer households are included in the sufficient category, and based on the criteria subyektif that 68.25 percent of pepper farmer households are included in the sufficient category. The factors that influence the level of household welfare of pepper farmers are the number of family members and income. Key words: farmers income, pepper, welfare